Redescription Cyrtodactylus lateralis (Werner) (Squamata: Gekkonidae) and Phylogeny of the Prehensile-tailed Cyrtodactylus - Harvey, Michael B.; O’connell, Kyle A.; Wostl, Elijah; Riyanto, Awal; Kurniawan, Nia; Smith, Eric N.; Grismer, L. Lee (Zootaxa, 2016)
We redescribe Cyrtodactylus lateralis (Werner) on the basis of new specimens. Cyrtodactylus lateralis is a prehensile-tailed species, known from scattered lowland to mid-elevation localities in northern Sumatra. The prehensile-tailed Cyrtodactylus are more speciose and have a wider distribution than previously thought. This group includes a mainland SE Asian clade consisting of C. elok, C. interdigitalis, and C. brevipalmatus and an insular clade containing C. durio, C. lateralis, C. nuaulu, C. serratus, C. spinosus, and C. stresemanni. However, a distinctive color pattern in the Wallacean and Papuan species and uncertainty surrounding the type locality of C. stresemanni raise unresolved questions about the inclusiveness of the insular clade. DNA sequence data supports a close relationship between C. elok and C. interdigitalis, but also reveals that C. lateralis and C. durio are not closely related to these species.